Coleridge's metaphors of being - Kessler, Edward, 1927- (Princeton legacy library., 1979)
In an original and provocative demonstration that Coleridge's later poetry took on a powerful metaphysical conception, Edward Kessler emphasizes Coleridge's struggle with language as a means of both expressing and creating Being. While many of Coleridge's late poems are generally viewed as fragments that constitute an aesthetic failure, Professor Kessler contends that what at first may appear to reflect Coleridge's inability to finish a poem can otherwise be seen as a deliberate rejection of what the poet came to see as a confining form. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.